Draft Fifth Five Year Plan (1974-79) (Volume IV) Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1974)
There will be 141 Primary Schools with an enrolment of 18,300 students by the end of Fourth Five Year Plan. 30 New junior Basic schools are proposed to be opened in addition to strengthening of existing schools. It has been decided to achieve 100% enrolment in the age group of 6-11 years by the end of 1975-76. Accommodation both residential and non-residential including clearing of back-log of Fourth Plan period is proposed to be made under Fifth Plan. Provision for supply of books, Publication of text books and midday Meals are also made.
Andaman and Nicobar Administration